Sociocultural Adaptation Strategies as Psychological Well-Being Predictors among Children of Foreign Citizens in Russia - V.V. Gritsenko; M.Y. Chibisova; N.V. Tkachenko; O.S. Pavlova; O.E. Khukhlaev (Moscow State University of Psychology and Education, 2023)
The aim of the study is to examine how the psychological well-being of children of foreign citizens is determined by their focusing on preserving the culture of their country of origin and accepting Russian culture, as well as by the level of expression of their national (Russian) and ethnic identity. Methods: Multidimensional Students’ Life Satisfaction Scale by E.S. Huebner, adapted by O.A. Sychev et al., Acculturation Scale for Children and Adolescents by O.E. Khukhlaev and M.Y. Chibisova, Measure of Youth’s Ethnic and National Identity, MYENI adapted by O.E. Khukhlaev, sociometric testing. The sample consisted of 669 children of foreign citizens, immigrants from the countries of Tajikistan, Uzbekistan, Kyrgyzstan, Kazakhstan, Ukraine, Armenia, Azerbaijan, aged 7 to 17 years. As a result of regression analysis, significant positive correlations between sociocultural adaptation and psychological well-being indicators were obtained in the sample of primary school, middle school and high school students. It was revealed that among primary and middle school students, integration strategy orientation serves as predictor of psychological well-being, while among high school students, such a predictor is assimilative strategy.